Detectable use of ENSO information on crop production in Southern Africa - Erin Coughlan de Perez; Weston Anderson; Eunjin Han; Gibbon Innocent Tirivanhu Masukwedza; Ntlele Mphonyane (Climate Services)
People have known that El Niño events are associated with low rainfall in Southern Africa for a century, and seasonal rainfall forecasts are now available in agricultural advisories for farmers. While there is abundant theory as to how farmers might (or should) use seasonal rainfall information on their farms, little is known about whether this information has been widely used or has had widespread benefit. In this study, we use subnational data on cropping area and yield to see if we can detect any macro-level patterns in agricultural choices or outcomes that are related to knowledge of the El Niño Southern Oscillation or seasonal forecast information in Southern Africa. We find that in Lesotho and parts of South Africa, planted area of maize and sorghum is reduced when there is a dry start to the season and an El Niño event is apparent at the time of planting. Similarly, we find that in both Lesotho and most provinces of South Africa, drought years associated with El Niño have worse yields than drought years that are not associated with El Niño (controlling for rainfall). This association could indicate that people are discouraged during El Niño years by the potential for drought, and they might be reducing cropping area, reducing agricultural investments, or turning to other income-generating activities. We are unable to detect a relationship between yields and the accuracy of seasonal rainfall forecasts, therefore we are unable to observe any additional yield benefit when more accurate seasonal forecast information is available.